Zerotier-Based Remote Access and Control for MiktoTik System - Rial Fauza (Brilliance: Research of Artificial Intelligence, 2026)
The ZeroTier features and menu on MikroTik have been available since RouterOS version 7, specifically introduced in version 7.1rc2 for the arm and arm64 architectures. ZeroTier offers a relatively simpler configuration process compared with traditional VPNs such as PPTP, L2TP, or IPsec. Administrators only need to install the ZeroTier service on the MikroTik device and the client, then enter the Network ID so the devices can connect to each other. This convenience provides time efficiency in the implementation of remote access networks. The research method was carried out through system design, MikroTik and ZeroTier configuration, and connection testing using client devices such as a computer and a smartphone. The results show that ZeroTier is able to build a virtual network that allows communication between the client and the MikroTik device as if they were on the same local network. In addition, this technology provides security through data encryption and easier configuration compared with traditional VPNs. Thus, ZeroTier can be an effective solution to support remote management and monitoring of MikroTik devices.